Experimental investigation of multilayered graphene systems for hydrogen storage. (30th August 2019) - Chauhan, Pawan Kumar; Vidhukiran, Venkataraman; Sujith, Ravindran; Parameshwaran, Rajagopalan
Abstract: The present work provides a comprehensive study of hydrogen uptake and storage in multilayered graphene systems, namely graphene nanoplatelets (GNP), supported by quantitative experimental investigations. For this purpose, a customized Sievert's Apparatus is fabricated to handle the cryogenic temperatures and pressures up to 5 bar. GNP was characterized using high resolution transmission electron microscopy, x-ray diffraction and Raman spectroscopy to determine the number of layers and presence of defects. Adsorption studies of molecular hydrogen on GNP have been conducted at three different temperatures of 298 K, 243 K and 99 K, all cases explored up to 2 bar pressure in the adsorption chamber. The maximum gravimetric density of 2.47 wt% have been observed at temperature of 99 K and 2 bar pressure. The nature of hydrogen storage between the GNP layers at different experimental conditions, its bearing on the quantity and stability is analyzed by developing a modified version of the expanded graphite model. Further, the improvement in the performance of the multi-layered graphene system is discussed and correlated experimentally to possible aiding of hydrogen storage through formation of physisorption channel.